2014
DOI: 10.4028/www.scientific.net/amm.567.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Soil Water Retention Functions for Humid Tropical Soils

Abstract: The determination of soil hydraulic properties is of paramount importance as they are needed in many models of water and solute transport in soils, however conventional methods are quite difficult, expensive and sometimes cumbersome to use. Most studies of soil water retention functions are for temperate soils and their soil water retention curve (SWRC) cannot be extrapolated to tropical region, as such this study focused solemnly on SWRC of soils of tropical region (Malaysia and Indonesia to be specific). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Three types of soil textures are studied in homogeneous soil slopes; the soil properties are shown in Table 1. The soil properties are taken from the lab experiments for soil case studies located in Malaysia and reported by Kassim et al (2012) at University Technology Malaysia, Skudai Campus, namely Bukit Cerapan and Babangida et al (2014). The fitting parameters for prediction hydraulic conductivity functions of soils using Van Genuchten method are as shown in Table 2.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Three types of soil textures are studied in homogeneous soil slopes; the soil properties are shown in Table 1. The soil properties are taken from the lab experiments for soil case studies located in Malaysia and reported by Kassim et al (2012) at University Technology Malaysia, Skudai Campus, namely Bukit Cerapan and Babangida et al (2014). The fitting parameters for prediction hydraulic conductivity functions of soils using Van Genuchten method are as shown in Table 2.…”
Section: Soil Propertiesmentioning
confidence: 99%